Artificial Intelligence for Better Inclusive Higher Education: A Study of a Private University in Cairo - Ismail, Shereen (AUC Knowledge Fountain, 2026)
This study explores how artificial intelligence (AI) tools relate to accessibility for visually impaired students in Egyptian higher education, focusing on University Y in Cairo. Grounded in the Social Model of Disability and Universal Design for Learning, it examines visually impaired students’ lived experiences of AI mediated access and the institutional conditions that shape these experiences. A qualitative phenomenological design was used, with semi-structured interviews conducted with visually impaired undergraduate students and key staff involved in assistive technology, teaching and learning, and student wellbeing; data were analyzed thematically. The findings indicate that participants experience AI tools (e.g., chatbots, transcription and image-description tools, AI-enhanced screen readers) as important mediators that help them access and interpret otherwise inaccessible materials, while also revealing persistent structural and pedagogical barriers and uneven institutional support. The study concludes that AI can contribute to more accessible and inclusive learning when integrated into a broader, UDL-informed institutional strategy that embeds accessibility in course design, strengthens staff development, and involves visually impaired students in shaping AI-related practices and decisions.